2016
DOI: 10.5599/jese.269
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of platinum-composite electrocatalysts prepared with different substrate materials

Abstract: Cyclic voltammetry (CV) measurements were conducted and analyzed for a preliminary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Although the CV of Pt/TiO2tt is typical for nanostructured Pt in acid solution, the registered CV currents were considerably lower in comparison to Pt/C composite counterpart, as it was already found during a preliminary investigation of the CV response stability. [27] The reported consideration indicate that only Pt from the surface of the agglomerates could contribute to the measured CV response (the loading of 7-nm-sized Pt particles [27] calculated from CV of Pt/TiO2tt (Figure 6) is only 3 wt. %).…”
Section: Electrochemical Properties Of Pt/tio2 From CV Responsementioning
confidence: 95%
See 1 more Smart Citation
“…Although the CV of Pt/TiO2tt is typical for nanostructured Pt in acid solution, the registered CV currents were considerably lower in comparison to Pt/C composite counterpart, as it was already found during a preliminary investigation of the CV response stability. [27] The reported consideration indicate that only Pt from the surface of the agglomerates could contribute to the measured CV response (the loading of 7-nm-sized Pt particles [27] calculated from CV of Pt/TiO2tt (Figure 6) is only 3 wt. %).…”
Section: Electrochemical Properties Of Pt/tio2 From CV Responsementioning
confidence: 95%
“…[27] It was found that the activity decreased upon cycling, which was more pronounced at lower sweep rates. This finding was assigned to less reversible Pt particles transformations at lower sweep rates, including agglomeration and coarsening, as the most probable cause.…”
Section: Introductionmentioning
confidence: 97%